1989
DOI: 10.1002/rrr.3450040108
|View full text |Cite
|
Sign up to set email alerts
|

Response of epiphytic diatom communities from the tailwaters of glen Canyon Dam, Arizona, to elevated water temperature

Abstract: The composition of epiphytic diatom communities from the cold tailwaters (12°C) of Glen Canyon Dam, Arizona, was analysed after a 2 wk incubation period at 12"C, 18°C and 21°C. There was a significant change in diatom composition between 12°C and 18"C, while no significant changes occurred between 18°C and 21°C. This suggests that a temperature threshold exists between 12°C and 18°C for the diatom flora in the tailwaters of Glen Canyon Dam. At the two higher water temperatures, smaller and closely adnate taxa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
1

Year Published

1993
1993
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 18 publications
2
11
1
Order By: Relevance
“…Stable isotope analyses (13C, "N) revealed that assimilated C and N in Gammarus collected at 14 Mile Bar originated from diatoms rather than from Oscillatoria, terrestrial detritus, or seston exported from Lake Powell (T. Angradi, unpublished data). Intact Cladophora has a high surface area which supports a dense assemblage of diatoms (Blinn et al, 1989). The most important ecosystem level function of attached Cladophora may be as a habitat for other organisms (Dodds and Gudder, 1992), and reach-wide disruption of this structural function due to exposure could precipitate higher trophic level effects within the Glen Canyon ecosystem.…”
Section: Discussionmentioning
confidence: 99%
“…Stable isotope analyses (13C, "N) revealed that assimilated C and N in Gammarus collected at 14 Mile Bar originated from diatoms rather than from Oscillatoria, terrestrial detritus, or seston exported from Lake Powell (T. Angradi, unpublished data). Intact Cladophora has a high surface area which supports a dense assemblage of diatoms (Blinn et al, 1989). The most important ecosystem level function of attached Cladophora may be as a habitat for other organisms (Dodds and Gudder, 1992), and reach-wide disruption of this structural function due to exposure could precipitate higher trophic level effects within the Glen Canyon ecosystem.…”
Section: Discussionmentioning
confidence: 99%
“…The plan proposes to release warm subsurface water (18-21Њ C) from Lake Powell into the Colorado River. In a study with circulation chambers, Blinn et al (1989) reported a significant change in the composition and physiognomy of the diatom epiphyte community on Cladophora at Lees Ferry between 12Њ and 18Њ C, with no significant change between 18Њ and 21Њ C. At the two higher temperatures, smaller and more closely attached taxa such as C. pediculus and Achnanthes spp. replaced D. vulgare and R. curvata in treatments at 12Њ C. Changes in community physiognomy of this nature may have major ramifications on the grazer community in the Colorado River, as previously discussed (Colletti et al 1987, Steinman et al 1987).…”
Section: Inflow and Reservoir Influence On Phytobenthosmentioning
confidence: 99%
“…Diatoms comprised > 95% of the algae in chironomid larvae guts at each location, and Cladophora fragments comprised < 1% of the total gut contents. The diatom genera most frequently encountered in chironomid guts were Achnanthes, Cocconeis, Cymbella, Diatoma and Rhoicosphenia, all of which are common epiphytes associated with Cladophora in this system (Czarnecki and Blinn, 1978;Blinn et al, 1989;Hardwick et al, 1992). Chironomid larvae …”
Section: Trophic Relationsmentioning
confidence: 98%
“…Warmer summer river temperatures may increase benthic invertebrate, and possibly macrophyte, diversity and production. However, warmer temperatures may also alter competitive hierarchies and the distribution of Cladophora, Oscillatoria, epiphytes and other macrophytes, thereby affecting the invertebrate food base and non-native fish populations in unpredictable ways (Blinn et al, 1989).…”
Section: Management Considerationsmentioning
confidence: 99%